2,6-Disubstituted Piperidine Alkaloids with Neuroprotective Activity from Hippobroma longiflora - Chen, Shu-Rong; Chen, Yih-Fung; Lin, Jue-Jun; Ke, Tzu-Yi; Lin, Yun-Sheng; Cheng, Yuan-Bin (Planta Medica, 2022)
Three new alkaloids, hipporidine A (1), hipporidine B (2), and (−)-lobeline N-oxide (3), were discovered from the whole plant of Hippobroma longiflora together with five known compounds (4–8). Their 2,6-disubstituted piperidine structures were established based on the HRESIMS, NMR (COSY, HMBC, HSQC, NOESY), and UV spectroscopic data. Hipporidines A (1) and B (2) possess a rare 1,3-oxazinane moiety. Compound 3 is the N-oxide derivative of (−)-lobeline (6). Moreover, the absolute configuration of norlobeline (5) was established by single-crystal X-ray diffraction analysis. Three major secondary metabolites (6–8) were evaluated for their neuroprotective effect against paclitaxel-induced neurotoxicity. Consequently, pretreatment with compound 8 at a concentration of 1.0 µM displayed significant attenuation on paclitaxel-damaged neurite outgrowth of dorsal root ganglion neurons without interfering with the cytotoxicity of paclitaxel on cervical cancer SiHa cells.
Keywords: Hippobroma longiflora; Campanulaceae; alkaloids; neuroprotective activity